2010
DOI: 10.1371/journal.pone.0009838
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Rat Neural Precursor Cells and Fibroblasts into Pluripotent Stem Cells

Abstract: BackgroundGiven the usefulness of rats as an experimental system, an efficient method for generating rat induced pluripotent stem (iPS) cells would provide researchers with a powerful tool for studying human physiology and disease. Here, we report direct reprogramming of rat neural precursor (NP) cells and rat embryonic fibroblasts (REF) into iPS cells by retroviral transduction using either three (Oct3/4, Sox2, and Klf4), four (Oct3/4, Sox2, Klf4, and c-Myc), or five (Oct3/4, Sox2, Klf4, c-Myc, and Nanog) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Later, cells were maintained without Dox in the PKCi culture condition. We also used the 2i/LIF culture condition as a positive control because earlier studies reported the successful establishment of riPSC cells with the 2i/LIF culture condition from differentiated rat cells (16,18). We found that the efficiency to derive rat iPSCs in the 2i/LIF condition is very low (two of five attempts were successful in the Weiss laboratory and zero of four attempts in the Paul laboratory, data not shown).…”
Section: Pkc Inhibition Facilitates Reprogramming Of Differentiated Ratmentioning
confidence: 99%
“…Later, cells were maintained without Dox in the PKCi culture condition. We also used the 2i/LIF culture condition as a positive control because earlier studies reported the successful establishment of riPSC cells with the 2i/LIF culture condition from differentiated rat cells (16,18). We found that the efficiency to derive rat iPSCs in the 2i/LIF condition is very low (two of five attempts were successful in the Weiss laboratory and zero of four attempts in the Paul laboratory, data not shown).…”
Section: Pkc Inhibition Facilitates Reprogramming Of Differentiated Ratmentioning
confidence: 99%
“…Chang et al reported differentiation of rat iPS cells into neurons of which approximately 10% were dopamine neurons, but the nature of the remaining population was not demonstrated. 10) To our knowledge, this is the first work identifying a population of glutamate neurons from riPSCs and furthermore demonstrating the neurons were responsive to agonist mediated stimulation. Indeed, it would be of great interest to study pharmacological glutamate neurotransmitter signaling using riPSCs derived neurons.…”
Section: Discussionmentioning
confidence: 85%
“…We subjected riPSCs to a multistep protocol 10) with modifications for converting iPSCs into neurons (Fig. 4A).…”
Section: Generation Of Ripscs and Analysis Of Pluripotencymentioning
confidence: 99%
“…As is has been previously proved that OSK combination is sufficient to successfully induce pluripotency on human fibroblasts [6,12,13] the aim of this work is only to compare the efficiencies obtained with the three proposed induction methods, and demonstrate that IRES structures in between the genes arrangement allows different levels of protein production in either version of ribonucleic acid used. Then, cells that are easily obtained from patients and have reliable dedifferentiation capabilities are desirable for a non-invasive patient-specific approach.…”
Section: Cellular and Molecular Medicine: Open Access Issn 2573-5365mentioning
confidence: 99%
“…However, many different combinations have been analyzed [2][3][4][5][6][7][8][9][10][11]. Even though efficiencies are still low, promising results have been obtained with the Oct4, Sox2 and Klf4 (OSK) combination [6, 12,13]. It is known that TFs stoichiometry influences dedifferentiation…”
Section: Introductionmentioning
confidence: 99%